2003
DOI: 10.7589/0090-3558-39.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Survey for Diseases in Free-Ranging Coyotes (Canis latrans) from Two Ecologically Distinct Areas of Utah

Abstract: The influence of habitat and associated prey assemblages on the prevalence of canine diseases in coyotes (Canis latrans) has received scant attention. From December 1997 through December 1999, we captured 67 coyotes in two ecologically distinct areas of Utah (USA): Deseret Land and Livestock Ranch and US Army Dugway Proving Ground. These areas differ in habitat and prey base. We collected blood samples and tested for evidence of various canine diseases. Prevalence of antibodies against canine parvovirus (CPV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
12
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
4
12
1
2
Order By: Relevance
“…McCue and O'Farrell (1988) reported CDV antibodies in 0-14% of the kit foxes sampled in California. We found that levels of CDV antibodies increased with age among both species, similar to results among coyotes in Texas (Guo et al, 1986), Wyoming (Gese et al, 1997), Arizona (Grinder and Krausman, 2001), and Utah (Arjo et al, 2003). The higher prevalence of CDV antibodies in adults may be a result of adults being more likely to survive exposure or adults having a longer exposure period to the virus and developing a persisting titer (Gorham, 1966;Green et al, 1984).…”
supporting
confidence: 68%
See 3 more Smart Citations
“…McCue and O'Farrell (1988) reported CDV antibodies in 0-14% of the kit foxes sampled in California. We found that levels of CDV antibodies increased with age among both species, similar to results among coyotes in Texas (Guo et al, 1986), Wyoming (Gese et al, 1997), Arizona (Grinder and Krausman, 2001), and Utah (Arjo et al, 2003). The higher prevalence of CDV antibodies in adults may be a result of adults being more likely to survive exposure or adults having a longer exposure period to the virus and developing a persisting titer (Gorham, 1966;Green et al, 1984).…”
supporting
confidence: 68%
“…The prevalence of CPV antibodies among San Joaquin kit foxes (V. macrotis mutica), a close relative of the swift fox (Mercure et al, 1993), ranged 67-100% in California (McCue and O'Farrell, 1988). The prevalence of CPV antibodies in coyotes from other western states (Arizona, Idaho, Utah, and Wyoming) was generally Ͼ70% (Thomas et al, 1984;Gese et al, 1997;Grinder and Krausman, 2001;Arjo et al, 2003). A high prevalence of antibodies is associated with a highly contagious, but nonfatal, infection, because prevalence is measured among survivors (Thomas et al, 1984).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We initially identified titers $32 as evidence of exposure to CDV and titers $25 as evidence of exposure to CPV-2 (Arjo et al 2003;Gese et al 2004). …”
mentioning
confidence: 99%